Financial Crises, Sovereign Risk and the Role of Institutions - Maltritz, Dominik; Berlemann, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
The recent world economic crisis showed very clearly that financial crises and sovereign defaults are severe threats to economic and social prosperity. In addition, it became apparent that currency crises and banking crises often occur together and are closely related to sovereign debt crises and defaults. The present book contains new research on various important issues related to financial crises and sovereign default risk by leading experts in the field. The book discusses new modelling approaches to financial crises, defaults and their interdependencies. It also sheds light on the consequences of different sorts of crises for the trust in the institutions which are concerned with managing them. Moreover, it provides discussions of several institutional features of the EMU and the world financial system and in particular the risks inherent in these institutions. The book also includes interesting suggestions for solving crises and improving financial stability.
Introduction -- Gold-backed Sovereign Bonds - An Effective Alternative to OMTs -- Trust in the European Central Bank Throughout the Worldwide Financial Crisis and the European Debt Crisis -- SIFIs in the Cross Sea - How Are Large German Banks Adjusting to a Rough Economic Environment and a New Regulatory Setting? -- The Endogenous Fragility at European Periphery -- The Danger of Tax Havens for Financial Stability -- The Evolution of International Geo-Political Risk 1956-2001 -- Financial Crises and Sovereign Default: Dependencies, Timing and Uncertainty in a Stochastic Framework -- The Risk of Withdrawals from the EMU and the Foreign Exchange Market -- An Economic Approach to Market Risk -- The Quantity Theory of Money in Year Six After the Subprime Mortgage Crisis.
Keywords: Economics; Europe -- Economic policy; International economics; Macroeconomics; Finance; Economics/Management Science; Financial Economics; Public Finance & Economics; Macroeconomics/Monetary Economics; European Integration; Finance/Investment/Banking.; International Economics